EVALUATION OF MAIZE HYBRIDS FOR MORPHO-QUANTITATIVE TRAITS UNDER PRAYAGRAJ AGRO-CLIMATIC CONDITIONS USING MAHALANOBIS D2 ANALYSIS - EDLA KIRAN (The Journal of Research ANGRAU, 2026)
The development and cultivation of hybrids is the key to improving the productivity of Maize crop. The present study evaluated 26 maize (Zea mays L.) hybrids under the agro-climatic  conditions of Prayagraj, Uttar Pradesh, during the Kharif season of 2024-2025 for genetic parameters and genetic variability in relation to yield and its morpho-quantitative traits. Analysis of variance (ANOVA) revealed significant differences among the hybrids, indicating substantial genetic variability. The traits field weight and biological weight recorded the high GCV (50.52 and  30.02) and PCV (50.96 and 30.25) values, respectively. The traits field weight, biological weight and plant height recorded the high heritability (>60%) along with high genetic advance expressed as a percentage of mean (>20%), suggesting predominant additive gene action and high potential for genetic improvement through selection.The assessment of genetic diversity grouped the 26 hybrids into 5 distinct clusters, with the majority (9 hybrids) falling into Cluster V. Among the clusters, the maximum intra-cluster distance was observed in Cluster V (3.6). The greatest intercluster distance (9.08) was observed between Cluster IV and Cluster I, suggesting that interbreeding among members in these two clusters could facilitate the production of highly desirable transgressive segregants. The pronounced inter-cluster distances, especially between Cluster IV and others, highlight its potential as a parent in heterotic cross combinations. Based  on a genetic divergence study VH171310, ZH22698, ZH20379 and VH183007. These finding offer crucial direction for selecting diverse and high-performing hybrids to enhance maize productivity and adaptability in Eastern Uttar Pradesh.